Perception Analysis of Ease of Use of BRImo Mobile Banking Application on Customer Satisfaction Through User Experience as a Mediation Variable (Survey of BRImo Customer Users in Sukabumi City) - Rifa Amalia Sukesna; Kokom Komariah; Resa Nurmala (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to analyze the influence of perceived ease of use on user satisfaction, mediated by user experience, among BRImo users in Sukabumi City. The research employs a quantitative method with an associative approach. The sample consists of 200 respondents who are BRImo users from seven sub-districts in Sukabumi City. Data was collected through a questionnaire distributed to all respondents, containing 24 statements related to the variables of perceived ease of use, user experience, and customer satisfaction. The collected data was then analyzed using validity and reliability tests with the help of SmartPLS 3.0 software. The results show that perceived ease of use has a positive and significant influence on customer satisfaction, user experience has a significant impact on customer satisfaction, and perceived ease of use positively and significantly affects user experience. Furthermore, the mediating effect of user experience in the relationship between perceived ease of use and customer satisfaction is proven to be significant.